Association of self-efficacy, risk attitudes, and time preferences with health-related quality of life and functioning after total hip or knee replacement – Results of the MobilE-TRA 2 cohort - Sebastian Fuchs; Lars Schwettmann; Benedict Katzenberger; Alexander Paulus; Boris Michael Holzapfel; Johanna Theresia Biebl; Martin Weigl (Health and Quality of Life Outcomes)
Abstract Background While total hip and knee replacement (THR/TKR) surgery are effective measures to restore functioning and reduce pain in patients with severe osteoarthritis (OA), long-term treatment effects vary among patients. Following behavioral economic theory, these differences may be partially attributed to the impact of personality traits on individual strategies to approach post-surgical challenges. This study explored the associations between self-efficacy, willingness to take risk regarding health (H-WTTR), and future orientation, and the 3-month course of health-related quality of life (HRQoL) and OA-specific health status. Methods As part of the prospective and observational MobilE-TRA 2 cohort study, 147 patients aged 60 years and older were assessed by self-administered questionnaires before and three months after THR/TKR at a single German hospital. As indicators for the surgical outcome, HRQoL was assessed by the EuroQol Five-Dimensional Five-Level Questionnaire (EQ-5D-5L), including the visual analogue scale (EQ-VAS), and functioning was assessed by the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) using the global score, function score, and pain score. All WOMAC scores were transformed into scales with 0 = worst health and 100 = best health. Self-efficacy was measured using the General Self-Efficacy Short Scale. H-WTTR and future orientation were assessed by single-item questions on 11-point Likert scales. The associations between these personality traits and the 3-month change in the outcome scores were analyzed using linear regression models for THR and TKR respectively. Results In THR patients a one-point-increase in self-efficacy was associated with improvements in EQ-5D-5L (β=0.0704; p=0.0099), WOMAC global (β=6.6337; p=0.0139), WOMAC function (β=8.2557; p=0.0046), and WOMAC pain (β=5.9994; p=0.0232). For TKR, only the association of self-efficacy with the EQ-VAS change-score was significant (β=5.8252; p=0.0482). Self-efficacy demonstrated weak positive, but not significant associations with all WOMAC scores and a negative association close to zero with the EQ-Index. H-WTTR and future orientation showed no significant associations to changes of the outcome scores. Conclusions Self-efficacy appears to be a prognostic factor for better THR/TKR outcomes after three months. If these findings can be confirmed in further research, strategies to improve self-efficacy should be considered in prehabilitation programs. Trial registration Not applicable.